Islamic Basic Education Planning in the Thematic Study of the Qur'an (Studies at SD/MI Level Units) - Siti Rahma Ismiatun; Mesiono Mesiono; Fachruddin Azmi; Deni Khurniawan; Qomaruddin Lubis (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the planning of Islamic basic education in the thematic studies of the Qur'an and hadith, this study is focused on the SD/MI level unit. This research uses a qualitative approach with a literature study method. The data of this research include studies of thematic interpretations, books and relevant scientific articles related to educational planning in QS. Al-Anfal verse 60 and QS. Al-Hasyr verse 18. The data sources were obtained from credible reference sources from the Google Scholar and Sinta pages. The results of this study conclude that the meaning of planning is interpreted as very important in QS. Al-Anfal: 60 and QS. Al-Hasyr: 18 as the first step in the whole process of life. Furthermore, planning also becomes an accurate “guiding compass” between the initial steps (main capital) and educational goals. Through this research, it is hoped that it will become a reference for relevant research related to rational and systematic analysis of the development of education based on the Qur'an.